Membongkar Kebijakan Dinas Perikanan Kabupaten Flores Timur dalam Pengelolaan Sumber Daya Perikanan - Leonardus Subang Koten (CV. Ulil Albab Corp, 2023)
Indonesia is famous for its marine and fisheries resources, therefore fisheries resource management is something that must be done through a policy program that can develop the potential of fisheries resources. This study aims to determine the management of fisheries resources by the Fisheries Service of East Flores Regency through policy programs including the fuel subsidy program for fishermen, the protection and empowerment program for small fishermen, the program to eat fish, and the capture fisheries program. The method in the research used a descriptive qualitative approach with data collection methods of observation, interviews, documentation and Focus Group Discussions. The research object in this study is to dismantle the Fisheries Service policy in managing fisheries resources. Primary data was collected through detailed interviews with 19 informants, namely policy makers and program managers at the Fisheries Service, village heads and several fishermen. Data analysis techniques in this research are data reduction, data presentation and conclusion drawing. The results showed that the management of fisheries resources in East Flores Regency is still not running optimally, this is because it is related to several fisheries agency programs that have not been evenly distributed in the East Flores Regency area, especially in Amagrapati Village, Ilepadung Village, Adabang Village. Because it still has shortcomings such as access to diesel fuel subsidies for fishermen, lack of counseling and empowerment of small fishermen, the Gemarin program has not been implemented evenly in the East Flores Regency area, and capture fisheries programs that have not been felt evenly by most fishermen in East Flores Regency who mostly still use simple equipment to go to sea.